1988
DOI: 10.1002/j.1460-2075.1988.tb02804.x
|View full text |Cite
|
Sign up to set email alerts
|

7SL RNA from Schizosaccharomyces pombe is encoded by a single copy essential gene

Abstract: We have identified an abundant ribonucleoprotein particle from Schizosaccharomyces pombe with properties related to those of the vertebrate signal recognition particle (SRP), including cytoplasmic localization, association with microsomes and ribosomes at low, but not high, salt concentrations and high resistance to micrococcal nuclease. The 256‐nucleotide RNA component carries a 5′‐triphosphate group and shows close secondary structure, and limited primary sequence homology to vertebrate 7SL RNA. 7SL‐like RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
1

Year Published

1988
1988
1997
1997

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 26 publications
0
36
1
Order By: Relevance
“…cerevisiae and yet 7SL-like molecules appear to be ubiquitous in other organisms (6,41,43), and (iii) that 7SL RNAs are RNA polymerase III transcripts (57) just as scRl appears to have signals for polymerase III transcription, we considered it worthwhile to examine the structure of scRl with reference to the known structures of 7SL RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…cerevisiae and yet 7SL-like molecules appear to be ubiquitous in other organisms (6,41,43), and (iii) that 7SL RNAs are RNA polymerase III transcripts (57) just as scRl appears to have signals for polymerase III transcription, we considered it worthwhile to examine the structure of scRl with reference to the known structures of 7SL RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The 7SL RNA gene of yeast appears to have an internal tRNA-like promoter (13). The plant 7SL genes may have evolved from these type 2 promoter-containing genes, perhaps explaining the internal B-box homology in the coding region of the Arabidopsis 7SL genes.…”
Section: -Gsmentioning
confidence: 99%
“…Mammalian SRP is an 11S particle composed of a 300-nucleotide RNA (7SL) and six polypeptides (28,29). Previous work in several laboratories led to the discovery of a ribonucleoprotein in the fission yeast Schizosaccharomyces pombe that is similar in size to mammalian SRP and contains a 254-nucleotide homolog of human SRP RNA (3,16,18). Disruption of the srp7 gene demonstrated that this RNA is essential for viability in S. pombe (3,18).…”
mentioning
confidence: 99%
“…Previous work in several laboratories led to the discovery of a ribonucleoprotein in the fission yeast Schizosaccharomyces pombe that is similar in size to mammalian SRP and contains a 254-nucleotide homolog of human SRP RNA (3,16,18). Disruption of the srp7 gene demonstrated that this RNA is essential for viability in S. pombe (3,18). The fission yeast homolog of mammalian SRP54 protein (SRP54p) (6) is also required for vegetative growth (1).…”
mentioning
confidence: 99%